Study of raw material of alfalfa yellow (like-sickle or Romanian) - O. V. Grechana; S. D. Trzhetsinskiy (Zaporozhye State Medical University, 2016)
Along with the wide distribution and use of alfalfa grass there is no comprehensive scientific pharmacognosy studies about representatives of the plants of this kind. Aim. To study the content of the group of true coumarins and 4-oxyderivatives which presence must be characteristic for the yellow alfalfa. Materials and methods. The determination of diagnostic anatomical features of the plant Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink has been carried out. The leaf petiole has such diagnostic characteristics: elongated epidermal cells, parenchymal or prosenchymal, 4-, or (rarely) 5-6 gonal; pubescence is of simple single-celled hairs with warty cuticle, which can be found on the upper and lower epidermis of the leaf. The stomatas are rare. The rosette is formed from basal epithelial cells near the base of the hairs. Results. 66 Components have been revealed by chromatography of native raw, 38 of components have been identified, namely - dihydrocoumarin (1.60%) and coumarin (13.13%). After the acid hydrolysis 52 components have been revealed, 41 of which have been identified. These substances are the complex of biologically active compounds: primary alcohols, aldehydes, ketones. 4-Oxycumarin derivatives have been identified: coumarin - 79.38% dihydrocoumarin - 4.95%, and 6-methylcoumarin - 0.39%. While studying the amino acid composition of the above-ground parts of alfalfa yellow we got interested in a significant amount of aspartic acid, proline and phenylalanine.